2000
DOI: 10.1093/emboj/19.11.2681
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the ORF-2 protein of the human respiratory syncytial virus M2 gene is initiated by a ribosomal termination-dependent reinitiation mechanism

Abstract: Translation of the open reading frame 2 (ORF-2) of the human respiratory syncytial virus M2 gene initiates at one of the three initiation codons located upstream of the termination codon for the first ORF. Replacement of ORF-2 with the major ORF of the chloramphenicol acetyltransferase reporter gene followed by systematic mutagenesis of the putative initiation codons demonstrated the usage of these codons as the translational initiators for ORF-2 expression both in vitro and in vivo. While the efficiency of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
95
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 40 publications
5
95
0
1
Order By: Relevance
“…A similar phenomenon was described for the subgenomic mRNA found in RHDVinfected cells where translation of ORF3 of the genome is coupled to termination of translation of the upstream ORF (18). In both cases, it was shown that the nucleotide sequence of the second downstream ORF was not essential for the process to occur because the virus ORF could be replaced with other sequences without an effect on the coupled translation (17,18). For the RSV study, the gene encoding bacterial chloramphenicol acetyltransferase (CAT) was substituted for the M2-2 gene (Fig.…”
supporting
confidence: 63%
See 4 more Smart Citations
“…A similar phenomenon was described for the subgenomic mRNA found in RHDVinfected cells where translation of ORF3 of the genome is coupled to termination of translation of the upstream ORF (18). In both cases, it was shown that the nucleotide sequence of the second downstream ORF was not essential for the process to occur because the virus ORF could be replaced with other sequences without an effect on the coupled translation (17,18). For the RSV study, the gene encoding bacterial chloramphenicol acetyltransferase (CAT) was substituted for the M2-2 gene (Fig.…”
supporting
confidence: 63%
“…Transfection and Reporter Assays-HEp-2 cells were transfected as described previously (17). The total amount of DNA added to each well was reduced to 250 ng, and the transfection reagent Lipofectin (Invitrogen) was used as recommended.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations